Operationalizing the Central Government Transfer Intercept Mechanism - Oosterman, Andre (World Bank, Washington, DC, 2017)
In October 2004, the Government of Indonesia (GOI) issued law 33/2004 concerning the Fiscal Balance between the central government and the regional governments. Like its predecessor, law 25-1999, the law stipulates a series of administrative sanctions that the Government may impose on regional governments that do not comply with certain of its provisions. These sanctions will take the form of a deferment or cut, depending on the specific nature of the non-compliance, in the general allocation (Dana Alokasi Umum or DAU) or shared revenues (Dana Bagi Hasil or DBH) to which the region would otherwise be entitled. The Ministry of Finance (MoF) is currently preparing a decree to operationalize this so-called intercept mechanism, and has requested the Decentralization Support Facility (DSF) to provide advice on the development of an effective DAU and DBH intercept mechanism. This final report presents the findings of a consultant ("the Consultant") contracted by DSF to provide this advice. Chapter two discusses administrative requirements to decrees and regulations that govern the allocation of DAU and DBH to regional governments, to ensure that the intercept mechanism remains effective. Chapter three describes the key features of an accounting mechanism that directs intercepted funds to the treasury, and remits the balance of the transfer to the defaulting regional government. The annex to this report contains the results of simulations the consultant has performed at the request of DJPK since the publication of the interim report.